Diagnostic Procedures, Treatments, and Outcomes in Stroke Patients Admitted to Different Types of Hospitals. Issue 3 (March 2015) - Asplund, Kjell; Sukhova, Maria; Wester, Per; Stegmayr, Birgitta
Abstract : Background and Purpose—: In many countries, including Sweden, initiatives have been taken to reduce between-hospital differences in the quality of stroke services. We have explored to what extent hospital type (university, specialized nonuniversity, or community hospital) influences hospital performance. Methods—: Riksstroke collects clinical data during hospital stay (national coverage 94%). Follow-up data at 3 months were collected using administrative registers and a questionnaire completed by surviving patients (response rate 88%). Structural data were collected from a questionnaire completed by hospital staff (response rate 100%). Multivariate analyses with adjustment for clustering were used to test differences between types of hospitals. Results—: The proportion of patients admitted directly to a stroke unit was highest in community hospitals and lowest in university hospitals. Magnetic resonance, carotid imaging, and thrombectomy were more frequently performed in university hospitals, and the door-to-needle time for thrombolysis was shorter. Secondary prevention with antihypertensive drugs was used less often, and outpatient follow-up was less frequent in university hospitals. Fewer patients in community hospitals were dissatisfied with their rehabilitation. After adjusting for possible confounders, poor outcome (dead or activities of daily living dependency 3 months after stroke) was not significantly different between the 3 types of hospital. Conclusions—: In a setting with national stroke guidelines, stroke units in all hospitals, and measurement of hospital performance and benchmarking, outcome (after case-mix adjustment) is similar in university, specialized nonuniversity, and community hospitals. There seems to be fewer barriers to organizing well-functioning stroke services in community hospitals compared with university hospitals. Abstract : Supplemental Digital Content is available in the text.